Form, Function, and Meaning of Mantras in the Bima Suna Ro Ndoso Tradition - Aryanah Hilman; Sutriani Asma; Radna Wismawati Yahya Sawek; Suchada Giaphong (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to analyze and describe the form, function, and meaning of incantations (mantra) used in the Suna Ro Ndoso traditional ceremony of the Bima ethnic group in Dompu District, Dompu Regency. Methodology: This qualitative research employed observation, interviews, and transcription methods for data collection. Data analysis was conducted using form analysis, function analysis, and hermeneutic interpretation. Research instruments included an audio recorder (mobile phone), field notes, and a structured interview guide with selected informants. Main Findings: The mantras in the Suna Ro Ndoso ceremony primarily take the form of gurindam (couplets) and free verse. Their functions include serving as prayers (permohonan), expressions of affection (pengasihan), healing (pengobatan), and consciousness-raising (penyadaran). The meanings conveyed are pleas for safety, surrender to God, facilitation of the ritual process, and healing for those believed to be possessed by spirits. Novelty/Originality of this study: This research provides the first specific and detailed documentation and analysis of the mantras within the Suna Ro Ndoso rite of the Bima people in Dompu. It contributes new empirical data to the study of oral literature and local wisdom, offering a deeper understanding of a cultural practice not previously examined in such focused detail.